The Mandalorian. The complete second season [videorecording (Blu-Ray)] - Favreau, Jon (Disney, 2023)
"The Mandalorian and the Child continue their journey, facing enemies and rallying allies as they make their way through a dangerous galaxy in the tumultuous era after the collapse of the Galactic Empire" -- Container.